Crashes on Financial Markets - Tran Dinh, Khanh (2016)
The aim of this work is description and analysis of the phenomena which suddenly cause unexpected and sharp decline in the financial markets, called crashes or collapses. This work is divided into theoretical and practical part. The theoretical part deals with the definition of the financial market and its crash, in addition, this part provides an overview of the theories explaining the origin of the speculative bubble and its bursting. The object of practical part is to describe occurred events in the financial markets in order to determine the possible causes, circumstances and consequences of these crashes.